Internalisasi Sikap Nasionalisme melalui Pembelajaran Sejarah di Sekolah - Nashihin, Nashihin; Muhyidin, Muhyidin; Afan Zaini, Ahmad (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2024)
Recently, we need to be wary of the condition of nationalism among students, several cases show students experiencing a nationalist identity crisis. These symptoms are reflected in the attitudes and behavior of students as the younger generation loves foreign culture more than their own culture. Nationalist values ​​are increasingly declining, such as not being able to recite the principles of Pancasila, the song Indonesia Raya and Bhinneka Tunggal Ika as well as a tendency to increase conflict and violence in resolving problems that occur between them. This research aims to explore the process of internalizing nationalist attitudes through history learning at school. The subjects of this research were students of Madrasah Aliyah Ma'arif 7 Banjarwati Paciran Lamongan using purposive sampling techniques. Data collection was carried out using interview, observation and documentation techniques. The research results show that the attitude of nationalism is internalized through three stages, namely 1) transformation of values ​​with an understanding of, among others, tolerance, responsibility, cooperation, love of peace, respect for differences; 2) value transactions are carried out by teachers by means of habituation, example, contextual examples and the use of learning media; and 3) transinternalization of values ​​is characterized by enthusiasm for learning, mutual respect, responsibility and the ability to work together as well as enthusiasm for achieving achievements and discipline in flag ceremonies and commemoration of national holidays.